The TESDA Institute for Green Skills - Soriano, Yndia Andrea P.; De Chavez, Kelvin C. (Quezon City College of Architecture, University of the Philippines Diliman, 2016)
In response to the increasing demand in green jobs, this thesis aims to uphold green TVET by creating a model center that will house TESDA's efforts to deliver quality education through green skills training. The design project shall be referred to as "The TESDA Institute for Green Skills." The study operates within the concept of two main development plans: (1) The Philippine Development Plan of 2011-2016, as strengthened by the Philippine Green Jobs Act of 2016; and (2) the TESDA's National Technical Education and Skills Development Plan for 2011-2016. The training programs to be offered by the proposed institute belong to sectors identified with high demand for such "green" skills/jobs and with high environmental impact. These fields include building and construction, transportation, and agriculture. The design process was approached in two ways: (1) the site as a form-giver, and (2) competency-based training (CBT) as a learning experience. Design translations were based on the concept of student-centric education, visual learning, and demonstration of mastery of skills.
includes appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Vocational training centers